Analysis of methods for efficient biodiversity conservation with focus on African cattle breeds - Reist-Marti, S.B.; Abdulai, A.; Simianer, H. (TSAP and ILRI, 2006)
Methods for biodiversity conservation are reported and applied to 49 African cattle breeds (26 taurine/sanga and 23 zebu/zenga (ZZ) breeds). It was estimated that about half of the breeds and half of today’s genetic diversity between breeds would be lost within 50 years. Based on a survey and a literature review, cost and effects of four conservation programmes were assessed: herd books combined with promotion of the breed (HB), in situ conservation with sire rotation (IS), cryoconservation of semen (CC) and in situ plus cryoconservation (IC). Conservation programmes involving strongly breeders, and giving them part of the responsibility for the conservation of the breed reduce endangerment. In this case Breeders were not just potential sellers of animals for a conservation program, but they participated actively in the program (e.g. take decisions) and took over part of the responsibility for the success of the program. It was shown that allocation of resources to only a subset of breeds is optimal. With US$ 2 million, 64% of the present diversity of the ZZ breeds could be maintained over 50 years, i.e. 13% more than if no action is taken.